Using Genome-Wide SNPs to Detect Structure in High-Diversity and Low-Divergence Populations of Severely Impacted Eastern Tropical Pacific Spinner (Stenella longirostris) and Pantropical Spotted Dolphins (S. attenuata) - Leslie, Matthew S.; Morin, Phillip A. (Frontiers in Marine Science, 2016)
Millions of spinner (Stenella longirostris) and pantropical spotted dolphins (Stenella attenuata) died since the 1960’s as bycatch in tuna nets in the eastern tropical Pacific Ocean. Despite three decades of protection, they show little-to-no sign of recovery (although recent fisheries-independent abundance estimates are not available). In efforts to establish biologically meaningful management boundaries for recovery, endemic subspecies and multiple stocks have been proposed. However, genetic differentiation among most of these units has been difficult to identify, possibly due to low statistical power stemming from large historical abundances, ongoing gene flow, and recent divergence. We tested for genetic structure at multiple hierarchical levels by analyzing the largest dataset to date brought to bear on these questions. Single nucleotide polymorphisms (SNPs) were collected from nuclear DNA regions associated with the restriction enzyme site PstI from 72 spinner dolphins and 58 pantropical spotted dolphins using genotype-by-sequencing (GBS). Our results support the current subspecies for both species and indicate stock-level separation for Tres Marias spinner dolphins and the two offshore pantropical spotted dolphin stocks in this area. Although bycatch has been reduced a small fraction of pre-protection levels, incidental mortality continues to impact these populations. Our results are important for the ongoing management and recovery of these highly-impacted pelagic dolphins in the eastern tropical Pacific Ocean.